Novel mGluR4 agonist Rapitalam ameliorates motor dysfunction in mice with tau-associated neurodegeneration - Natalia V. Avdeeva (Belgorod National Research University, 2020)
Introduction: Tau protein is classically involved in the pathogenesis of a neurodegenerative processes, such as Parkinson's disease. This study was aimed at testing the novel mGluR4 selective agonist using it in transgenic mice with tau-associated neurodegeneration. Materials and methods: Mice with Human P301S Tau hyperexpression were divided into 3 groups: Rapitalam 6 mg/kg and 20 mg/kg by gavage 3 times a week; and Control (Sham). The motor functions of animals were evaluated at 12th, 14th, 16th, 18th, and 20th weeks of life using the grip-test, rotarod and hanging wire test. In addition, the time of symptoms onset and death was recorded. Research results: The use of Rapitalam at a dose of 6 mg/kg and 20 mg/kg significantly restored the holding impulse on a hanging wire, increasing it from 5.06±1.25 kg×sec to 6.42±0.97 kg×sec and 8.84±1.17 kg×sec, respectively. A similar trend was observed in the grip test: Rapitalam recovered grip strength from 28.43±5.04 N in the control group to 44.27±5.54 N (6 mg/kg) and 59.53±7.95 (20 mg/kg). Finally, the two-month use of Rapitalam neither delayed the manifestation of symptoms, nor increased the survival of mice. Discussion: The cause of the loss of nerve cells in the mouse-tau line is autophagy. Apparently, Rapitalam is not able to simulate this process by reducing excitotoxicity, but against the background of the neurodegenerative process, it increases the activity of the nerve cells. Conclusion: Rapitalam improves motor dysfunction in mice with tauopathy, with no effect on the survival of animals.